Dietary Moringa oleifera fruit powder improves antioxidant capacity, intestinal development, and gut microbiota in lion-head geese - Wang, L.; Yan, Y.; Cao, Q.; Chen, W.; Shah, A.M.; Chen, J.; Zhao, Y.; Ma, Y.; Jiang, J.; Li, Z.; Lukuyu, Ben A.; Jiang, X.; et al. (Chinese Association of Animal Science and Veterinary Medicine, 2026)
Moringa oleifera fruit powder (MOFP) is a natural source of bioactive compounds with various health-promoting properties. However, limited research has investigated its effects on growth performance, intestinal development, and lipid regulation in lion-head geese. In this study, 900 healthy 1-day-old lion-head goslings (male:female = 1:1; initial body weight = 119.21 ± 0.091 g) were randomly assigned to six treatments, each with six replicates of 25 birds. Geese were fed a basal diet (control) and diets supplemented with MOFP at 2%, 4%, 6%, 8%, or 10% for 21 days. The results showed no significant differences in growth performance among all groups. Levels of serum globulin, aspartate aminotransferase, and blood urea nitrogen (BUN) exhibited significant difference among dietary MOFP usages (P < 0.05). Notably, the 4% MOFP group showed optimal glutathione peroxidase activity (P = 0.009), while total antioxidant capacity increased linearly with MOFP dosage (P < 0.001). Histomorphometric results showed that dietary inclusion of 4% MOFP significantly increased ileal villus length (P < 0.01) and decreased ileal muscle thickness (P < 0.001) compared with the control group. Meanwhile, 4% MOFP significantly elevated melatonin levels in the ileal mucosa. 16S rRNA sequencing analysis indicated that the 4% MOFP group had significantly higher relative abundances of Rothia, Corynebacterium, and Proteiniclasticum in the ileum at the genus level, compared with the control and 8% MOFP groups (P < 0.05). In conclusion, dietary supplementation with 4% MOFP effectively enhanced antioxidant capacity, promoted intestinal development, and modulated gut microbiota composition, thereby contributing to improved health status in geese. These findings provide a scientific foundation for the potential application of MOFP as a functional feed ingredient in goose production.